A user satisfaction model for mobile government services: a literature review - Abdulla Jaafar Desmal; Suraya Hamid; Mohd Khalit Othman; Ali Zolait (PeerJ Computer Science, 2022)
User satisfaction is essential for the success of an organisation. With the development of government service delivery through mobile platforms, a compatible measurement model must be found to measure user satisfaction with performing such services through a mobile government portal. Measuring user satisfaction with mobile government services is necessary nowadays due to the increasing popularity of smart devices. Research on mGovernment users’ satisfaction is lacking, leading to difficulties in understanding users’ expectations. In the present study, systematic literature reviews have been used to analyze users’ satisfaction with mGovernment portals and propose a comprehensive model compatible with such contexts. The results show that government agencies can evaluate users’ satisfaction using the proposed model of six quality constructs: usability, interaction, consistency, information, accessibility, and privacy and security. The study recommends improving the evaluation strategies of mGovernment portals regularly to ensure they fit with challenges. Measuring user satisfaction at mGovernment services encourages the user to perform the transactions through such online platforms, increasing the digitalization process and reducing the cost and efforts for both the service provider and end-users.